(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
An old dream about a route through the Tehuantepec Isthmus, which linked the Gulf of Mexico and the Pacific Ocean, came true between 1858 and 1860, when American entrepreneurs set up a new business including steamboats, wagons and carriages, mules and horses, round trip transportation for travelers, freight and mail. The dream did not last long, but this route attracted businessmen, speculators, technicians and immigrants who wanted to get to California and benefit from the gold findings. This work deals with the itinerary and its stages, approaching travelers through the few existing testimonies, many of which belong to the press, both Mexican and American, because this issue has not been entered upon academically.